RESOURCE OPTIMIZATION OF CYCLIC PROCESSES "LINEAR" TYPE OPERATION OF AIR TRANSPORT COMPLEX - Міщенко, А. В. (Science-based technologies, 2014)
The resource optimization of cyclic processes "linear" type operation of air transport industry has been сonsidered. Two interpretations maximization problem "group" resource productivity has been сonsidered. Definitely a vector which is a plan of resources distribution in operations process, for each operation required "specialized" resources or funds to ensure its application. Displaying ensure feasibility plan of distribution "specialized" air transport resources in complex heterogeneous operations of the functioning of air transport infrastructure.